2016
DOI: 10.1590/abd1806-4841.20164635
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of nail lichen planus and lichen planus pigmentosus

Abstract: We describe a fifty-six-year old, Afro-descendent female patient showing dystrophy of her twenty nails and hyperchromic, asymptomatic macule on her face. Histopathological examination of the macule showed vacuolization of the basal layer, melanophages in the superficial dermis and lymphoplasmocytic inflammatory infiltrate. Nail biopsy revealed orthokeratotic hyperkeratosis and lichenoid inflammatory infiltrate. Lichen planus pigmentosus is an uncommon variety of lichen planus. It is characterized by typical hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It most commonly affects female individuals with high skin phototypes (Fitzpatrick skin phototypes III to VI) and it is rarely seen in fair-skinned people [3, 4]. In this work, we describe a postmenopausal female patient with late-stage frontal fibrosing alopecia (FFA) and facial LPPig involving the upper eyelids.…”
Section: Introductionmentioning
confidence: 99%
“…It most commonly affects female individuals with high skin phototypes (Fitzpatrick skin phototypes III to VI) and it is rarely seen in fair-skinned people [3, 4]. In this work, we describe a postmenopausal female patient with late-stage frontal fibrosing alopecia (FFA) and facial LPPig involving the upper eyelids.…”
Section: Introductionmentioning
confidence: 99%
“…Pterygium, anonychia, erythronychia, red lunula, trachyonychia, and splinter hemorrhagia may also be observed [3,10]. Nail involvement in LPP or FFA is rarely reported [2,4,11]. The nail findings presented by our patient were the most commonly seen nail changes in LP.…”
Section: Discussionmentioning
confidence: 76%
“…Various nail signs, including longitudinal ridging, onycholysis, pterygium, onychoatrophy, and anonychia may be seen [3]. Rare cases of nail LP and LPP coexistence have been reported [2, 4].…”
Section: Introduction/literature Reviewmentioning
confidence: 99%
“…LPP can impact the patient's quality of life due to its chronic and progressive remissions and exacerbations from 6 months to 3 years [ 12 ]. Previous studies reported that LPP can occur with lichen planus (LP), as active or resolving LP lesions can be found in patients with LPP [ 5 , 13 ]. LPP also coexists with other variants of LP such as lichen planopilaris [ 14 ] and oral lichen planus (OLP) [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%